Notes: (3) An Arrowhead of Rhyolitic Ash from Linlithgow, West Lothian - Robertson, Anne S (Proceedings of the Society of Antiquaries of Scotland, 1943)
The arrowhead was discovered in 1899 among the roots of an upturned tree. It is shouldered but not barbed, and has a tang for insertion in a shaft. The shoulders are slightly rounded and form obtuse angles with the tang. The source of material is likely to be one of the groups of rhyolitic lavas in the Pentland Hills.